Antibacterial activity of Novel \(β\)-Lactam moieties on \(α\)-Hemolytic Streptococcus - G, Swaroop; Golding, Bernard; Baisch, Ulrich; Kirk, Gary; Karakaraddi, Ashwini; K S, Prathibha (International Journal of Pharmacology and Toxicology, 2013)
Synthesis of novel \(β\)-lactam antibiotic drug moieties deals with the bicyclic compound, aim to improve the good antibacterial activity. The \(β\)-lactam antibiotics moieties were synthesised via coupling of a range of acids such acetyl salicylic acid; benzoic acid; phenoxyacetic acid to the \(β\)-lactam backbone moiety of 6-aminopenicillanic acid (6-APA). Initially various coupling methods were investigated and optimised for Model amide reactions (i) NHS/DCC, (ii) EDC (iii) Mixed anhydride reactions respectively, followed by deprotection of penicillin by BOC derivatives. Study of Kinetics on Benzyl Penicillin (BP) was carried out to detect the rate of hydrolysis of the drug. The synthesized antibacterial drugs were administered on \(α\)-Hemolytic StreptococcusÂ bacterial species for the bioassay studies through zone of inhibition method.